Risk assessment : tools, techniques, and their applications - Ostrom, Lee T.; Wilhelmsen, Cheryl A., 1933- (Hoboken, New Jersey : Wiley, 2012)
"All the tools needed to perform a thorough risk assessment-whether you're working in insurance, forensics, engineering, or public safetyRisk analysis is the method of analyzing the dangers to individuals, businesses, and government agencies posed by potential natural and man-made hazards. The central task of the risk assessor is predicting the success of a project. This includes isolating the entire spectrum of adverse events that can derail a project or threaten the health and safety of individuals, organizations, and the environment. Designed as a practical, in-the-field toolkit, Risk Assessment details every aspect of how a risk assessment is performed, showing the proper tool to be used at various steps in the process, as well as locating the tool that best fits the risk assessment task at hand. Examining not only the very nature of risks and consequences, with fascinating historical examples, the book progresses from simple to more complex risk assessment techniques used by the authors in their daily work, all presented in a form that can be readily adapted to any number of real-life situations: Ecological Risk Assessment Task Analysis Techniques Preliminary Hazards Analysis Failure Mode and Effects Analysis Human Reliability Analysis Critical Incident Technique With numerous industry-specific case studies, as well as additional case studies for risk assessments for a restaurant and a process plant, the book provides readers with complete examples of how each of the techniques can be used in a variety of real-world situations. Including downloadable worksheets and other useful assessment materials, as well as guidance on using PRA software, this unparalleled reference offers all the tools and techniques needed to conduct a thorough and accurate assessment of risk"--
Machine generated contents note: 1. Introduction to Risk Assessment 2. Risk Perception 3. Risks and Consequences 4. Ecological Risk Assessment 5. Task Analysis Techniques 6. Preliminary Hazards Analysis 7. Primer on Probability and Statistics 8. Developing Probabilities 9. Failure Mode and Effects Analysis 10. Human Reliability Analyses 11. Critical Incident Technique 12. Event Tree and Decision Tree Analysis 13. Critical Function Analysis 14. Basic Fault Tree Analysis Technique 15. Probabilistic Risk Assessment 16. Qualitative and Quantitative Research Methods Used in Risk Assessment 17. Vulnerability Analysis Technique 18. Developing Risk Model for Aviation Inspection and Maintenance Tasks 19. Risk Assessment and Community Planning 20. Risk of an Epidemic 21. Process Plant Risk Assessment Example 22. Industry Specific Case Studies 23. Restaurant Risk Assessment Case Study 24. Glossary 25. Acronyms.
Περιέχει ευρετήριο.
Keywords: Risk assessment -- Statistical methods; Probabilities; Technology; Engineering